Las modificaciones a la ley de bancos y la crisis financiera - Avendaño Cisneros, Juan Luis; Merino Nuñez, Fernando; Pizarro Aranguren, Luis; Peschiera Mifflin, Diego (IUS ET VERITAS, 2008)
El artículo no presenta resumen.